2023
DOI: 10.1111/1477-8947.12284
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous effects of urbanization and environment Kuznets curve hypothesis in Africa

Abstract: This work explores the heterogeneous effect of urbanization and nonrenewable energy consumption on the environment in 54 African nations. Panel data were used from 1996 to 2019. For estimation, panel quantile regression analysis, augmented mean group, panel threshold regression, and the environment Kuznets curve hypothesis were applied to check the relationship between income and carbon emissions. The study's outcome demonstrates that urbanization and nonrenewable energy consumption degrade the environment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The finding further suggests that individuals in the urban centers of East Africa adopted sophisticated and modern technologies that are more carbon-intensive due to their rising income levels, thereby offsetting environmental quality. Hussain et al (2023) supported this finding by confirming urbanization as harmful to environmental quality in 54 African nations, while Opoku Marfo et al ( 2023) reported a similar finding for Ghana. However, Khan and Khan (2023) found a nonlinear relationship between urbanization and environmental pollution in Belt and Road Initiative countries, while Tawfeeq (2023) discovered a negative association between urbanization and CO 2 emissions in the United States.…”
Section: Discussion Of the Resultsmentioning
confidence: 78%
“…The finding further suggests that individuals in the urban centers of East Africa adopted sophisticated and modern technologies that are more carbon-intensive due to their rising income levels, thereby offsetting environmental quality. Hussain et al (2023) supported this finding by confirming urbanization as harmful to environmental quality in 54 African nations, while Opoku Marfo et al ( 2023) reported a similar finding for Ghana. However, Khan and Khan (2023) found a nonlinear relationship between urbanization and environmental pollution in Belt and Road Initiative countries, while Tawfeeq (2023) discovered a negative association between urbanization and CO 2 emissions in the United States.…”
Section: Discussion Of the Resultsmentioning
confidence: 78%
“…Thus, the conceptual framework of Klaus and Kiehl [24] depends on finding "species-rich and well-functioning urban ecosystems". Arguably, such urban design should also include incorporation of elements that reduce climate change, such as increased reliance on renewable energy as African cities develop [96] as well as greater attention to biological constituents. Whenever possible, we advocate the use of genetic stock from known local settings, perhaps helping offset losses in nearby sites.…”
Section: Improving the Biodiversity And Other Contributions Of Citiesmentioning
confidence: 99%
“…In contrast, the STIRPAT model enhances the IPAT framework by allowing for the inclusion of a broader range of indices in the analysis of influence factors, thereby offering a more flexible and comprehensive approach. This model has become a prevalent method in contemporary environmental research [31][32][33][34]. The basic formulation of the STIRPAT model is as follows:…”
Section: The Stirpat Modelmentioning
confidence: 99%